Treatment of chronic non-specific (musculoskeletal) back pain - V. A. Parfenov; V. A. Golovacheva; A. I. Isaikin; A. A. Golovacheva; E. V. Silina (Неврология, нейропсихиатрия, психосоматика)
Treatment of patients with chronic non-specific back pain (CNBP) is an important issue not only in medicine, but also in modern society as a whole, as it is associated with significant socio-economic burden.The lecture presents the most common anatomical sources of CNBP, the causes of CNBP and issues of differential diagnosis. Much attention is paid to the basic principles of therapy for CNBP: drug therapy, kinesiotherapy and psychological methods. Clinical observations are presented that demonstrate the effectiveness of a multimodal integrated approach to the treatment of CNBP based on the use of cognitive behavioral therapy, educational programs and kinesiotherapy and self-monitoring test tasks.